Determination of the interventions of families intended for the symptoms of children with cancer. Issue 3 (June 2017) - Bektas, Murat; Kudubes, Aslı Akdeniz; Bektas, İlknur; Altan, Sema Sal; Selekoglu, Yasemin
Abstract: Background: The presence and the severity of the symptoms that result from cancer and its treatment adversely affect the quality of life, mood, and daily activities of both the patient and the health care providers. Objective: This study aims to determine the use of interventions by families intended for the relief of symptoms in children with cancer. Methods: The Children and Parents Information Form and Form of Interventions used in the Symptom Management were used to collect the data. The data of the study were evaluated as percentages, means by using chi-square test. In all analyses, 5% significance level was used. Results: Among the children, 49% were female and 50.8% were male. There was a statistically significant difference between the interventions of parents regarding the symptoms of children with cancer according to the stage of the disease ( p  < .001). Conclusion: It is very important that health professionals prepare a training plan that evaluates the symptoms of a child with cancer with a holistic approach, and share this plan to parents.